2022
DOI: 10.1038/s41467-022-32003-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating effects of parents’ cognitive and non-cognitive skills on offspring education using polygenic scores

Abstract: Understanding how parents’ cognitive and non-cognitive skills influence offspring education is essential for educational, family and economic policy. We use genetics (GWAS-by-subtraction) to assess a latent, broad non-cognitive skills dimension. To index parental effects controlling for genetic transmission, we estimate indirect parental genetic effects of polygenic scores on childhood and adulthood educational outcomes, using siblings (N = 47,459), adoptees (N = 6407), and parent-offspring trios (N = 2534) in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 95 publications
0
51
1
Order By: Relevance
“…The correlations obtained from the mother-child dyads were statistically significant or close to statistical significance and were higher than for the father-child dyads. In general, the correlations estimated in our study were somewhat lower than those typically reported in previous research with nongifted community samples ( Anger and Heineck 2010 ; Calderon and Hoddinott 2010 ; Demange et al 2022 ; Grönqvist et al 2010 ). One factor that may have limited the magnitude of the correlations in our study might be traced to the rank restriction of total IQ, which we used as an entry criterion in the study.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The correlations obtained from the mother-child dyads were statistically significant or close to statistical significance and were higher than for the father-child dyads. In general, the correlations estimated in our study were somewhat lower than those typically reported in previous research with nongifted community samples ( Anger and Heineck 2010 ; Calderon and Hoddinott 2010 ; Demange et al 2022 ; Grönqvist et al 2010 ). One factor that may have limited the magnitude of the correlations in our study might be traced to the rank restriction of total IQ, which we used as an entry criterion in the study.…”
Section: Discussioncontrasting
confidence: 97%
“…These results appear to be consistent with data reported in the literature that compared the cognitive abilities of mothers and fathers with those of their typically developing children. More specifically, it was found that mothers’ cognitive abilities (e.g., executive functioning, working memory, verbal IQ) correlated with children’s cognitive abilities, whereas fathers’ non-cognitive abilities (e.g., academic motivation, perseverance, mindsets, learning strategies, and social skills) correlated with their children’s cognitive abilities (e.g., Demange et al 2022 ; Grönqvist et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as all current findings are based on 8-year-olds of European ancestry in a Norwegian cohort, it is unknown to what extent these effects are present in other populations and at other developmental periods. For example, differences in the importance of genetic nurture effects on childhood educational achievement between Dutch and British samples were observed in a recent study [ 33 ]. Given that environmental influences on mental health may vary across communities and developmental stages, it is plausible that potential indirect genetic effects could be of differential importance in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Our models controlled for principal components of population stratification, so residual population structure is unlikely to explain our results. Another mechanism could be assortative mating and dynastic effects from the grandparent generation or via sibling effects [43]. Future studies should use larger samples of multi-generation families or imputed grandparental genotypes to investigate this hypothesis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%